Current-conveyor-based single-element-controlled and current-controlled sinusoidal oscillators - Fongsamut, C.; Anuntahirunrat, K.; Kumwachara, K.; Surakampontorn, W. (My University, 2006)
A new single-element-controlled sinusoidal oscillator circuit that incorporates two second generation current conveyors (CCIIs), two grounded capacitors and two resistors is presented and analysed. The circuit is beneficial to monolithic integrated circuit implementation by the use of grounded capacitors. In addition, a new current-controlled sinusoidal oscillator using only two second generation current controlled conveyors (CCCIIs) and two grounded capacitors can be achieved by replacing CCIIs and resistors series at X terminals with CCCIIs. The oscillators provide extremely low passive 0 -sensitivities and good frequency stability. Moreover, the oscillation frequencies of the CCII-based and the CCCII-based oscillators can be controlled, respectively, by a grounded resistor and by an external bias current. Experimental and SPICE simulation results that confirm the theoretical predictions are given.
Keywords: CCCII; CCII; Current controlled conveyor; Current conveyor; Oscillator